Does Music Training Enhance Literacy Skills? A Meta-Analysis - Gordon, Reyna L.; Fehd, Hilda M.; McCandliss, Bruce D. (Frontiers in Psychology, 2015)
Children’s engagement in music practice is associated with enhancements in literacy-related language skills, as demonstrated by multiple reports of correlation across these two domains. Training studies have tested whether engaging in music training directly transfers benefit to children’s literacy skill development. Results of such studies, however, are mixed. Interpretation of these mixed results is made more complex by the fact that a wide range of literacy-related outcome measures are used across these studies. Here, we address these challenges via a meta-analytic approach. A comprehensive literature review of peer-reviewed music training studies was focused on rigorous criteria needed to test the direct transfer hypothesis, including: a) inclusion of music training versus control groups; b) inclusion of pre vs. post comparison measures, and c) indication that reading instruction was held constant across groups. Twelve studies were identified (n= 901). Two classes of outcome measures emerged with sufficient overlap to support meta-analysis: phonological awareness and reading fluency. Hours of training, age, and type of control intervention were examined as potential moderators. Results supported the hypothesis that music training leads to gains in phonological awareness skills. The effect isolated by contrasting gains in music training versus gains in control was small relative to the large variance in these skills (d=0.2). Interestingly, analyses revealed that transfer effects for rhyming skills tended to grow stronger with increased hours of training. In contrast, no significant aggregate transfer effect emerged for reading fluency measures, despite some studies reporting large training effects. The potential influence of other study design factors were considered, including intervention design, IQ, and SES. Results are discussed in the context of emerging findings that music training may enhance literacy development via changes in brain mechanisms that support both music and language cognition.